2014
DOI: 10.1007/s11745-014-3923-6
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Solubility and Oral Bioavailability of γ‐Tocotrienol Using a Self‐Emulsifying Drug Delivery System (SEDDS)

Abstract: The aim of this study was to evaluate the in vitro and in vivo performance of γ-tocotrienol (γ-T3) incorporated in a self-emulsifying drug delivery system (SEDDS) and to compare its enhanced performance to a commercially available product, namely Tocovid Suprabio™ (hereafter Tocovid), containing tocotrienols. The solubilization of γ-T3 was tested in a dynamic in vitro lipolysis model followed by in vitro cellular uptake study for the lipolysis products. In addition, in vitro uptake studies using Caco2 cells we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
28
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(30 citation statements)
references
References 39 publications
2
28
0
Order By: Relevance
“…A recent study reported the bioavailability of γ-tocotrienol, δ-tocotrienol versus annatto-based γ-tocotrienol (10%) + δ-tocotrienol (90%) dissolved in SEDDS using rats and displayed that γ-tocotrienol (10%) and δ-tocotrienol (90%) showed bioavailability of 332 (0.05 mg/kg) and 31.5 (0.5 mg/kg) for low doses, and bioavailability was 4.5 ± 0.1 (2.5 mg/kg) and 3.0 ± 0.1 (25 mg/kg) at higher doses, due to nonlinear absorption kinetics [ 11 ]. The results of γ- tocotrienol dissolved in SEDDS versus commercial Tocovid were also reported in vitro and in vivo in rats [ 22 ]. The in vitro results showed two-fold increase in the solubilization as well as higher cellular uptake while in vivo studies showed two-fold improvement in oral bioavailabity of γ-tocotrienol in SEDDS formulations compared to Tocovid [ 22 ].…”
Section: Discussionmentioning
confidence: 97%
“…A recent study reported the bioavailability of γ-tocotrienol, δ-tocotrienol versus annatto-based γ-tocotrienol (10%) + δ-tocotrienol (90%) dissolved in SEDDS using rats and displayed that γ-tocotrienol (10%) and δ-tocotrienol (90%) showed bioavailability of 332 (0.05 mg/kg) and 31.5 (0.5 mg/kg) for low doses, and bioavailability was 4.5 ± 0.1 (2.5 mg/kg) and 3.0 ± 0.1 (25 mg/kg) at higher doses, due to nonlinear absorption kinetics [ 11 ]. The results of γ- tocotrienol dissolved in SEDDS versus commercial Tocovid were also reported in vitro and in vivo in rats [ 22 ]. The in vitro results showed two-fold increase in the solubilization as well as higher cellular uptake while in vivo studies showed two-fold improvement in oral bioavailabity of γ-tocotrienol in SEDDS formulations compared to Tocovid [ 22 ].…”
Section: Discussionmentioning
confidence: 97%
“…Further studies investigated the incorporation γ-and δ-tocotrienol in self-emulsifying drug-delivery systems (SEDDS) on their bioavailability. Findings of these studies showed a significant increase in the solubility, permeability, and oral bioavailability of γ-and δ-tocotrienols both in vitro and in vivo (67,86). To explain the enhanced intestinal permeability and bioavailability of γ-and δ-tocotrienol delivered as either SLN or SEDDS compared with their delivery as mixed micelles, in vitro mechanistic studies were performed (67,85,86).…”
Section: Strategies To Improve Vitamin E Oral Bioavailabilitymentioning
confidence: 99%
“…Findings of these studies showed a significant increase in the solubility, permeability, and oral bioavailability of γ-and δ-tocotrienols both in vitro and in vivo (67,86). To explain the enhanced intestinal permeability and bioavailability of γ-and δ-tocotrienol delivered as either SLN or SEDDS compared with their delivery as mixed micelles, in vitro mechanistic studies were performed (67,85,86). Results of these studies revealed that packaging γ-and δ-tocotrienol in SLN or SEDDS delivery systems were able to enhance both isoforms' intestinal permeability and bioavailability as a result of the enhanced passive permeability and reduced contribution of NPC1L1 to the transport of both isoforms (67,85,86).…”
Section: Strategies To Improve Vitamin E Oral Bioavailabilitymentioning
confidence: 99%
See 2 more Smart Citations